Macrophage and Tumor Cell Cross-Talk Is Fundamental for Lung Tumor Progression: We Need to Talk - Sarode, Poonam; Schaefer, Martina Barbara; Grimminger, Friedrich; Seeger, Werner; Savai, Rajkumar (Frontiers in Oncology, 2020)
Regardless of the promising results of certain immune checkpoint blockers, current immunotherapeutics have met a bottleneck concerning response rate, toxicity, and resistance in lung cancer patients. Accumulating evidence forecasts that the crosstalk between tumor and immune cells takes center stage in cancer development by modulating tumor malignancy, immune cell infiltration, and immune evasion in the tumor microenvironment (TME). Cytokines and chemokines secreted by this crosstalk play a major role in cancer development, progression, and therapeutic management. An increased infiltration of Tumor-associated macrophages (TAMs) was observed in most of the human cancers, including lung cancer. In this review, we emphasize the role of cytokines and chemokines in TAM-tumor cell crosstalk in the lung TME. Given the role of cytokines and chemokines in immunomodulation, we propose that TAM-derived cytokines and chemokines govern the cancer-promoting immune responses in the TME and offer a new immunotherapeutic option for lung cancer treatment.